2024
DOI: 10.3233/jrs-230034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between proactive and retroactive models of medication reconciliation in patients hospitalized for acute decompensated heart failure

Davoud Ahmadimoghaddam,
Paniz Akbari,
Maryam Mehrpooya
et al.

Abstract: BACKGROUND: Most research on the impact of medication reconciliation on patient safety focused on the retroactive model, with limited attention given to the proactive model. OBJECTIVE: This study was conducted to compare the proactive and retroactive models in patients hospitalized for acute decompensated heart failure. METHODS: This prospective, quasi-experimental study was conducted over six months, from June to November 2022, at the cardiology unit of an academic hospital in Iran. Eligible patients were tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The authors from Iran compared medication reconciliation models in an elegant prospective six months quasi-experimental study of over 1100 medication reconciliations and showed the advantages of the proactive model as a timely and effective method of medication reconciliation, particularly in improving medication safety for high-risk patients [4].…”
mentioning
confidence: 99%
“…The authors from Iran compared medication reconciliation models in an elegant prospective six months quasi-experimental study of over 1100 medication reconciliations and showed the advantages of the proactive model as a timely and effective method of medication reconciliation, particularly in improving medication safety for high-risk patients [4].…”
mentioning
confidence: 99%